Global Kidney Exchange: Analysis and Background Papers from the Perspective of the Right to Health - Bey, Kiaryce (2017)
Global Kidney Exchange (GKE) is a program aimed at facilitating trans-national kidney donation. Although its proponents aim at reducing the unmet demand of kidneys in the United States through the trans-nationalization of kidney exchange programs, the World Health Organization (WHO) and The Transplantation Society (TTS) have expressed concerns about its potential effect on black markets of organs and transnational organ trafficking, as well as on low- or middle-income countries health systems. For GKE to be implemented, it would need to be permitted to operate in at least some low- or middle-income countries. What are the right to health implications of GKE’s implementation? With the aim of answering this question, the eighteen University of Denver students in the First Year Seminar course I taught in autumn 2017 with the title “The Right to Health in Theory and Practice”, identified and researched the different aspects that would affect this issue, and produced the analysis we present in this report. Based on our analysis, the potential right to health implications of GKE are: First, the program may improve timely access to organ donation primarily to patients with health insurance in the United States. Second, a large-scale implementation of the program may have a positive impact on health costs savings, which potentially could benefit the United States health system. Third, on a global health level, the program relies on existing health inequalities among countries in terms of funding, human resources, and health system strengthening, and it is likely to exacerbate those inequalities. Fourth, the program has the potential of negatively affecting the efforts that low- and middle-income countries are already doing to address end-stage renal failure, including the improvement of their own organ donation systems. Finally, given what we have learned about the current situation of organ trafficking, it is easy to think that GKE would unintentionally end up being linked to chains of organ trade. The only way how a program like GKE could have a positive impact from a right to health perspective is if it establishes local partnerships that have the effect of decreasing health inequalities. Additionally, we identified some issues of concern that are beyond the level of influence of local authorities: the unmet demand of kidneys in high-income countries is a reality that incentivizes organ trade and transplant tourism, and this is a problem in need of solutions; transnational organ trafficking as well as human trafficking with the purpose of organ donation are problems that need more visibility; for a global exchange of organs to be implemented, it would need to rely on supranational or transnational regulation and oversight; and the global epidemic of chronic kidney disease needs to be addressed through a public health perspective that emphasizes prevention